Ideological Essentialization of Afghan Women in Hosseini's A Thousand Splendid Suns (The Batuk, 2020)
This article analyses the representation of women in Khaled Hoesseini’s novel A Thousand Splendid Suns (2003). This novel foregrounds the Afghan history in the aftermath of the fall of monarchy and the subsequent Russianinvasion, rise of Taliban and the arrival of the US after 9/11. All these events resulted in ethnic cleansing, hunger, mass exploitation, displacement and physical and psychological trauma to the common people especially the poor, women, and children. They brought eternal political instability to the ancient nation. The article uses the feminist lens of interpretation and concludes that the novel presents a graphical picture of Afghan women, their sufferings, their fight against the social and political patriarchy and biasness, their pain, human values and struggle for dignity.